MATHEMATICAL MODELING OF THE RESULTS OF THE PROCESS OF OBTAINING ARENES IN THE EXTRACTION - Jurayeva Laylo Raxmatillayevna (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: The article describes of the chemical and oil and gas industry, the processing of various organic wastes, and the localization of products are urgent issues.